Correlation between Language Screening Test and Frenchay Aphasia Screening Test for Aphasia Screening in Ischemic Stroke - Febryanto, Dwi; Yudiatma, Muh. Firman; Widiawatie, Noni; Retnaningsih, Retnaningsih; Handayani, Fitria; Anggraini, Ria (Research and Community Service Unit, Poltekkes Kemenkes Kupang, 2024)
Aphasia is a communication disorder that occurs after brain damage. Delays in diagnosing aphasia can lead to depression, decrease quality of life, and raise hospital stays and costs. Ischemic stroke aphasia screening instruments have been widely developed but are still difficult to interpret. Nowadays, the Language Screening Test (LAST) is reportedly quick, easy to understand, straightforward, and suitable for use by nurses. However, the LAST subtests are different from the Frenchay Aphasia Screening Test (FAST), which has been used in the past to evaluate aphasia. This study aims to determine the relationship between LAST and FAST in ischemic stroke aphasic patients for aphasia screening. The study used an analytic observational method with a cross-sectional approach. The population in this study were stroke patients at Tugurejo Semarang Hospital who had their CT Scan checked. The sample was taken using a purposive sampling technique. Bivariate data analysis with Spearman Rank Correlation test. We obtained 50 samples 19 male patients and 31 female patients with the highest age range of 51-60 years as many as 26 patients. The highest Education and profession is primary school and housewife. Patients who experienced aphasia with LAST and FAST scored as many as 27 and 29 people, while the rest not have aphasia. The Spearman's Rank test obtained p-values of 0,000 and < 0,05 respectively. Meanwhile, the correlation coefficients of LAST and FAST on aphasia were 0,678 and 0,678 respectively. There is a positive correlation between the LAST and FAST in ischemic stroke aphasic patients for aphasia screening. Nurses can use the LAST instrument to collect data and establish nursing diagnoses of verbal communication disorders.